Developing Life Skills In Primary School Students - Sanjar Qurbonov (Euro Asian Journal Publishing, 2024)
This article discusses the development of life skills in primary school students, along with some key methods and approaches to effectively carry out this process.
Keywords: life skills; project-based learning; problem-based learning